(untitled) (Bangladesh Journal of Plant Taxonomy, 2018)
Crepispalaestina subsp. babcockii Inceer & Aksu Kalmuk subsp. nov. (Asteraceae, Cichorieae) is described and illustrated. It grows in shady places and red pine forest in southwest Anatolia, Turkey. The chromosome number of the new subspecies is 2n = 2x = 8. The diagnostic morphological characters that distinguish C. palaestina subsp. babcockii from morphologically similar taxa C. palaestina subsp. palaestina and C. pulchra are discussed, and a conservation status for the new taxon is suggested. Bangladesh J. Plant Taxon. 25(1): 45-49, 2018 (June)